Demanding Energy Space, Time and Change (Springer International Publishing, 2018)
This edited collection critically engages with an important but rarely-asked question: what is energy for? This starting point foregrounds the diverse social processes implicated in the making of energy demand and how these change over time to shape the past patterns, present dynamics and future trajectories of energy use. Through a series of innovative case studies, the book explores how energy demand is embedded in shared practices and activities within society, such as going to music festivals, cooking food, travelling for business or leisure and working in hospitals. Demanding Energy investigates the dynamics of energy demand in organisations and everyday life, and demonstrates how crucial an understanding of spatiality and temporality is in order to grasp the relationship between energy demand and everyday practices. This collection will be of interest to researchers and students in the fields of energy, climate change, transport, sustainability and sociologies and geographies of consumption and environment. Chapters 1 and 15 of this book are available open access under a CC BY 4.0 license at link.springer.com.